EKSPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) PADA MATERI OPERASI BENTUK ALJABAR DITINJAU DARI KECERDASAN EMOSIONALKELAS VII SMP NEGERI SE-KAB LOMBOK UTARA TAHUN AJARAN 2015/2016 - Hasanah, A.K Uswatun; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objectives of this research were to investigate: (1) which learning model of the NHT, TPS, and direct learning models (2) which emotional intelligence of the low, moderate, and high emotional intelligences results in a better learning (3) in each learning model, which emotional intelligence of the low, moderate, and high emotional intelligences results in a better learning (4) in each emotional intelligence, which learning modelÂ  of the NHT, TPS, and direct learning models results in a better learning achievement. This research used the quasi experimental research method with the factorial design of 33. Its population was all of the students in Grade VII of State Junior Secondary Schools of North Lombok Regency in Academic Year 2015/2016. The samples of research were determined by using the stratified cluster random sampling technique. They consisted of 309 students, namely: 103 in Experimental Class 1; 102 students in Experimental Class 2; and 104 in Control Class. The data of research were collected through questionnaire of emotional intelligence and test of learning achievement. The technique of analyzing the data use two-ways ANOVA with unbalanced cells. The results of research are as follows: 1) The NHT learning model results in a better learning achievement in Mathematics than the TPS and the direct learning model. 2) The learning achievement in Mathematics of the students with the high emotional intelligence is better than that of the students with the moderate emotional intelligence. 3) In the NHT learning model, the students with the high emotional intelligence have a better learning achievement in Mathematics than those with the moderate and low emotional intelligences, and the students with the moderate emotional intelligence have a better learning achievement in Mathematics than those with the low emotional intelligence. 4) In the high emotional intelligence, the NHT learning model results in the same learning achievement in Mathematics as the TPS learning model.Key words: Numbered Heads Together, Think Pair Share, Direct Learning, and Emotional Intelligence.